PENGARUH DOSIS PUPUK ORGANIK DAN DOLOMIT PADA LAHAN PASIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max, L.Merrill) - Widodo Saputro; Rahayu Sarwitri; Pantja Siwi V.R. Ingesti (Universitas Tidar, 2017)
This research studied he effect of organic fertilizer and dolomite in the land of sand o the growth and yield of soybean (Glycinemax, L. Merrill). this research was conducted on may 2012 and completed in Ketawang village, Grabag district, Purworejo regency with altitude of 6 meters above sea level, on the type of soil acidity regosol. This research used a factorial exsperiment with a complete rendomized block design (RCBD) consists of 2 factor treatment and repeated in three times. The factor that was dosis dolomite (D) which consists of three levels, namely 0,1,2 tons/ha. The second factor shisako with organic fertilizer levels is 0,2.5,5 tons/ha. The results showed that increasing the dose of dolomite did not increase plant height, number of pods per plant, pod dry weight, weiht of crop seeds, rood dry weight, dry weight of stover, in creasing fertilizer shisako has no effect on all the parameters of observation. There is no interection between dolomite and fertilizer dose shisako on all parametes.